THE IMPACT OF TAXATION UNDERSTANDING, TAX SANCTIONS, AND TAX MORALITYON THE COMPLIANCE OF INDIVIDUALS’ TAX OBLIGATIONS - Alifvia Arubah Shofaa; Effriyanti (Adisam Publisher, 2024)
This study aims to analyze the impact of taxation understanding, tax sanctions, and tax morality on the compliance of individuals’ tax obligations. The type of research is quantitative with an associative approach. The population of this research is Taxable Personal Registered KPP Pratama Pondok Aren. The sampling technique used was accidental sampling. Testing the hypothesis using double linear regression analysis with the help of the statistical tool SPSS 27. The results of the data testing in the study showed that simultaneously, the impact of tax comprehension, tax sanctions, and tax morals influenced the compliance of individuals with their tax obligations.